2018
DOI: 10.1007/s00590-018-2201-3
|View full text |Cite
|
Sign up to set email alerts
|

TEN versus external fixator in the management of pediatric diaphyseal femoral fractures: evaluation of the outcomes

Abstract: This study showed that TENS and external fixation have similar results in term of fracture healing and complication, even if patients treated with TENS are more satisfied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…in children [16][17][18] . For example, Rollo et al 19 showed that humeral fracture patients treated with TEN are more satisfied compared with external fixation. Compared with traditional surgical methods, TEN has superior value to plate fixation with less blood loss, shorter operative time, and less economic loss 20 .…”
Section: Introductionmentioning
confidence: 99%
“…in children [16][17][18] . For example, Rollo et al 19 showed that humeral fracture patients treated with TEN are more satisfied compared with external fixation. Compared with traditional surgical methods, TEN has superior value to plate fixation with less blood loss, shorter operative time, and less economic loss 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Open reduction and internal fixation for metaphyseal fractures may lead to implant loosening, failure of internal fixation and infection, causing nonunion and severe malunion. Surgical treatment should be avoided [6]. This patient was hospitalized with right femoral osteomyelitis at the age of 2, and imaging examination revealed an occult right tibial epiphyseal fracture (type IV).…”
Section: Discussionmentioning
confidence: 98%
“…Currently there is no effective treatment options for this disease, mostly symptomatic therapy [7]. The recurring low-energy fractures put the children under severe psychological pressure and increased the economic burden on the family and society.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm renders bacteria highly tolerant to antibiotics and host defenses [6][7][8]. Unfortunately, infections of the orthopedic-traumatological surgical site are very common in children [9] and in the elderly [10][11][12][13][14][15][16][17][18][19][20].The aim of our work is to verify if there are differences between pathogens, and treatment between the two groups most susceptible to skin infections by means of synthesis such as children and the elderly.…”
Section: Introductionmentioning
confidence: 99%